Validation of Neutral Wind in the Mesopause Measured by a Dual‐Channel Optical Interferometer (DCOI) Network of the Chinese Meridian Project - W. J. Liu; Y. J. Zhu; J. Y. Xu; Q. Z. Li; W. Yuan; G. Y. Zhu; T. C. Wang; G. T. Yang; L. F. Du; S. Y. Liu; F. Q. Li (Space Weather, 2025)
Abstract A Dual‐Channel Optical Interferometer (DCOI) based on Asymmetric Spatial Heterodyne Spectroscopy technique has been deployed at 11 stations by Phase II of the Chinese Meridian Project, establishing a ground‐based network for routine neutral wind measurement in upper mesosphere and thermosphere over China. Neutral winds measured by the DCOI network in mesopause region were compared with average‐weighted neutral winds from co‐located meteor radar and sodium (Na) lidar in three stations. The DCOI winds are in a good agreement with meteor radar and Na lidar observations and the largest correlation coefficient reaches up to about 0.92. These results validate DCOI as a robust instrument for wind measurements in the mesopause region. The operational DCOI network will provide unprecedented spatiotemporal coverage of wind measurements in the mesopause for studying dynamic processes.